2022
DOI: 10.1093/advances/nmac077
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Nuts and Seeds and Health Outcomes Including Cardiovascular Disease, Diabetes and Metabolic Disease, Cancer, and Mortality: An Umbrella Review

Abstract: Consumption of nuts and seeds is associated with a range of health outcomes. Summarizing the best evidence on essential health outcomes from the consumption of nuts is essential to provide optimal recommendations. Our objective is to comprehensively assess health outcomes associations related to the consumption of nuts and seeds, using a culinary definition including tree nuts and peanuts (registered in PROSPERO: CRD42021258300). Health outcomes of interest include cardiovascular disease, cancer, diabetes, obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 139 publications
(97 reference statements)
1
46
0
Order By: Relevance
“…A more recent 2022 umbrella review assessing the role of nuts in preventing several chronic diseases found similar associations with CVD incidence and mortality [ 21 ]. For CVD incidence, 11 cohort comparisons were assessed (including 376,228 participants and 18,655 events), and a 19% lower risk was observed comparing high to low consumption (RR = 0.81, CI: 0.74–0.89) and 21% lower risk when assessing associations per serving (28 g/day) (RR = 0.79, CI: 0.70–0.89).…”
Section: Nuts and Cardiovascular Disease Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent 2022 umbrella review assessing the role of nuts in preventing several chronic diseases found similar associations with CVD incidence and mortality [ 21 ]. For CVD incidence, 11 cohort comparisons were assessed (including 376,228 participants and 18,655 events), and a 19% lower risk was observed comparing high to low consumption (RR = 0.81, CI: 0.74–0.89) and 21% lower risk when assessing associations per serving (28 g/day) (RR = 0.79, CI: 0.70–0.89).…”
Section: Nuts and Cardiovascular Disease Outcomesmentioning
confidence: 99%
“…For CVD incidence, 11 cohort comparisons were assessed (including 376,228 participants and 18,655 events), and a 19% lower risk was observed comparing high to low consumption (RR = 0.81, CI: 0.74–0.89) and 21% lower risk when assessing associations per serving (28 g/day) (RR = 0.79, CI: 0.70–0.89). For CVD mortality, 16 cohort comparisons were included (524,610 participants and 19,574 cases), and a 25% lower risk comparing high to low consumption (RR = 0.75, CI: 0.71, 0.79) was observed and a 6% lower risk when assessing nut intake by 28 g/day (RR = 0.94, CI: 0.93, 0.96) [ 21 ]. This umbrella review also assessed dose-response relationships with CVD mortality and found that the optimal intake levels of nuts are ~15–20 g/day and that there were limited further benefits of consuming up to one serving (28 g/day), similar to the earlier meta-analysis [ 22 ].…”
Section: Nuts and Cardiovascular Disease Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies reportd that, a water extract blocked the growth of rat prostate carcinoma and a hot water extract of the entire plant inhibited the development of mammary tumors in mice. Numerous in vitro studies have also demonstrated the anti-cancerous and anti-leukemic activity of bitter melon against numerous cell lines including liver cancer, human leukemia, melanoma and solid sarcomas [46] . Digestive system: Leaf juice is purgative and emetic.…”
Section: Isolation Of Charantinmentioning
confidence: 99%
“…While there are many studies focusing on the association of nuts and seeds consumption with prevalence of different diseases, less is known about the seeds themselves. Studies have linked high intake of nuts and seeds with lower risk of cardiovascular diseases, diabetes, and cancer mortality but they usually include only more popular types of nuts and seeds, like walnut, almond, hazelnut, pecan, pistachio, macadamia, quinoa, sesame, sunflower seed, chia, pumpkin seed, flaxseed, or hemp seed [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%